2019
DOI: 10.1186/s12868-019-0518-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk and encoding-related hippocampal connectivity in older adults

Abstract: Background Cardiovascular conditions contribute to brain volume loss, reduced cerebrovascular health, and increased dementia risk in aging adults. Altered hippocampal connectivity has also been observed in individuals with cardiovascular conditions, yet the functional consequences of these changes remain unclear. In the present study, we collected functional magnetic resonance imaging data during memory encoding and used a psychophysiological interaction analysis to examine whether cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“… 32 In fact, a recent functional magnetic resonance imaging study found cardiovascular risk to be associated with altered hippocampal-medial prefrontal coupling when completing a memory encoding task. 33 In line with this, we also found that WHx MI made more errors in placing items during the immediate trial of the RCFT. This could indicate subtle spatial memory impairments, in which WHx MI remember pieces of the figure, but spatial location of those pieces, which are thought to be highly governed by hippocampal place cells, seemed to be an issue.…”
Section: Discussionsupporting
confidence: 82%
“… 32 In fact, a recent functional magnetic resonance imaging study found cardiovascular risk to be associated with altered hippocampal-medial prefrontal coupling when completing a memory encoding task. 33 In line with this, we also found that WHx MI made more errors in placing items during the immediate trial of the RCFT. This could indicate subtle spatial memory impairments, in which WHx MI remember pieces of the figure, but spatial location of those pieces, which are thought to be highly governed by hippocampal place cells, seemed to be an issue.…”
Section: Discussionsupporting
confidence: 82%
“…The frontal lobe, cuneate lobe, anterior cuneate lobe, cingulate gyrus, hippocampus, and parahippocampal gyrus belong to the default mode network (DMN). Extensive studies have shown that the DMN is sensitive to nervous system diseases and can be destroyed in the early stage, which may also be one of the reasons for the decrease in cognitive function in patients with CSVD ( Meusel et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…27,28 For example, 1 study linked higher Framingham risk scores with smaller brain volumes in PWoH across the age spectrum. 27 Similarly, a study of 38 male PWH and 37 PWoH showed that elevated Framingham risk scores were associated with larger volume of white matter hyperintensities, a biomarker of cerebral small vessel disease. 28 Conversely, 1 study observed that CVD variables were not associated with gray matter or white matter brain volumes.…”
Section: Discussionmentioning
confidence: 99%
“…These results complement previous studies associating Framingham scores with changes in neuroimaging in PWH. 27,28 For example, 1 study linked higher Framingham risk scores with smaller brain volumes in PWoH across the age spectrum. 27 Similarly, a study of 38 male PWH and 37 PWoH showed that elevated Framingham risk scores were associated with larger volume of white matter hyperintensities, a biomarker of cerebral small vessel disease.…”
Section: Discussionmentioning
confidence: 99%